2019
DOI: 10.1111/1744-9987.13395
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lower Past‐Year Serum Sodium and Hyponatremia on Depression Symptoms and Cognitive Impairments in Patients With Hemodialysis

Abstract: The relationship between hyponatremia, depression symptoms, and cognitive impairments in patients receiving hemodialysis treatment remain unclear. This study aimed to examine the impact of past‐year average serum sodium levels on current depression symptoms and cognitive impairments in patients receiving hemodialysis, with adjustment for possible confounders. A total of 200 participants were recruited for this study. Depression symptoms and cognitive impairments were assessed using the Patient Health Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Significant correlations were discovered between CI, depression symptoms, and serum sodium levels. Furthermore, such differences have been observed in hyponatraemia of any severity (moderate to severe) [37]. The following study discovered a link between impaired functional status and mild chronic hyponatremia [38].…”
Section: Markers Related To Uremic Toxinsmentioning
confidence: 69%
See 1 more Smart Citation
“…Significant correlations were discovered between CI, depression symptoms, and serum sodium levels. Furthermore, such differences have been observed in hyponatraemia of any severity (moderate to severe) [37]. The following study discovered a link between impaired functional status and mild chronic hyponatremia [38].…”
Section: Markers Related To Uremic Toxinsmentioning
confidence: 69%
“…Trail Making Test Part B Digit Symbol Substitution Test [36] Hyponatremia correlated with symptoms of depression. 200 HD Patient Health Questionnaire Perceived Deficit Questionnaire-5 [37] Plasma phosphorus level (>6 mg/dL, p = 0.034), inadequate dialysis dose (Kt/V < 1, 2, p = 0.023) and hyponatremia (Na < 135 mEq/L, p = 0.001) infuenced poor executive and functional status. Anemia correlated with CI (increase in Hb values improved cognitive functions); improvement in Hb (p < 0.05) correlated with cerebral artery blood flow.…”
Section: Hd 180 Hcmentioning
confidence: 99%
“…Patients undergoing HD can experience symptoms such as lassitude, pain, muscle cramps, nausea, vomiting, constipation, diarrhea, rash, skin dryness, sleep disorders, depression, anxiety, and emotional and sexual problems after the treatment [1,2]. Many chronic HD patients do not feel well after the treatment sessions and need some time to recover.…”
Section: Introductionmentioning
confidence: 99%
“…While KD + PL group met dietary guideline RDA for sodium, previous literature suggests that KDs may require a higher intake of sodium due the natriuretic effects of the diet (O'Donnell et al, 2014;Volek et al, 2021). Hyponatremia has a known association with depressive mood in clinical populations (Fan et al, 2020;Suárez et al, 2020). Indeed, our findings showed that supplementation with KS containing a proprietary combination of minerals elicited subjective mood amelioration, reflected here as lower depression and higher happiness scores (Figure 3), particularly when compared to subjects following a KD without KS.…”
Section: Discussionmentioning
confidence: 99%